Pengoptimalisasian Kecerdasan Kinestetik Anak Usia 5-6 Tahun Melalui Senam Cerdas Ceria Siswa RA Melyaz - Rizky Windi Lestari; Novita Friska (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This study aims to evaluate good behavior and critical thinking in children of group B aged 5-6 years. This study is a class action study (PTK) carried out in two phases of the pre-cycle, cycle I and cycle II, this study represents a new breakthrough in the world of education for children of 5-6 years, the study conducted interviews with 13 children revealed that 23.1% of them had low criteria, while 76.9% had high criteria for good behaviour. No child meets the high criteria in good behavior. Group B children part I do not meet the high quality criteria, while the rest meet the criteria with the proportion of five children (38.44%) and eight children (61,56%). The study also found that 11 children (84.6%) showed good critical thinking, and 2 children (15.4%) fulfilled critical thought rules, with none of them having critical thoughts rules. According to Gardner's theory, optimal cognitive development can be achieved by focusing on activities such as actors, athletes, or dancers, and repetition is an effective method to enhance critical thinking in children aged 5-6 years. The results of the study show that the quality of the child's physical examination improved significantly in 2022/2023, especially in parts I and II